FALSE CONFESSIONS IN NIGERIAN POLICE CUSTODY: A THEORETICAL AND LITERATURE-BASED CRITICAL ASSESSMENT - Enenta, Francisca Nkechi (African Journal of Social and Behavioural Sciences, 2025)
This study critically examines the issue of false confessions among suspects in police custody, focusing on the psychological, social, and systemic factors contributing to this phenomenon, particularly within Nigeria’s criminal justice system. Through a theoretical and literature-based review, the paper explores how coercive interrogation methods, authority pressure, and psychological vulnerability lead to false confessions. Drawing on key theoretical frameworks, including Psychological Coercion Theory, Social Influence Theory, Cognitive Dissonance Theory, and Labeling Theory, the study synthesizes evidence suggesting that prolonged interrogations, the absence of legal representation, and manipulation tactics such as promises of leniency or threats of harm are significant factors in producing false confessions. The review also highlights the vulnerability of certain suspect groups, such as minors or individuals with cognitive impairments, and the exacerbating role of weak institutional safeguards and poor training for investigators. Key recommendations include adopting video-recorded interrogations, requiring the presence of legal counsel during questioning, and enhancing police officer training in ethical, evidence-based interrogation techniques. This theoretical review underscores the need for systemic reforms in policing practices, particularly in developing countries like Nigeria, to reduce the incidence of false confessions and protect the integrity of the justice system.